Multi-wavelength spectroscopic analysis of the ULX Holmberg II X-1 and its nebula suggests the presence of a heavy black hole accreting from a B-type donor - Reyero Serantes, S.; Oskinova, L.; Hamann, W. -R.; Gómez-González, V. M. A.; Todt, H.; Pauli, D.; Soria, R.; Gies, D. R.; Torrejón, J. M.; Bulik, T.; Ramachandran, V.; Sander, A. A. C.; et al. (EDP Sciences, 2025)
Context. Ultra-luminous X-ray sources (ULXs) are high-mass X-ray binaries with an X-ray luminosity above 1039 erg s−1. These ULXs can be powered by black holes that are more massive than 20 M⊙, accreting in a standard regime, or lighter compact objects accreting supercritically. There are only a few ULXs with known optical or ultraviolet (UV) counterparts, and their nature is debated. Determining whether optical/UV radiation is produced by the donor star or by the accretion disc is crucial for understanding ULX physics and testing massive binary evolution.
Aims. We conduct, for the first time, a fully consistent multi-wavelength spectral analysis of a ULX and its circumstellar nebula. We aim to establish the donor star type and test the presence of strong disc winds in the prototypical ULX Holmberg II X-1 (Ho II X-1). Furthermore, we aim to obtain a realistic spectral energy distribution of the ionising source, which is needed for robust nebula analysis. We acquired new UV spectra of Ho II X-1 with the Hubble Space Telescope (HST) and complemented them with archival optical and X-ray data. We explored the spectral energy distribution of the source and analysed the spectra using the stellar atmosphere code PoWR and the photoionisation code CLOUDY. Our analysis of the X-ray, UV, and optical spectra of Ho II X-1 and its nebula consistently explains the observations. We do not find traces of disc wind signatures in the UV and the optical, rejecting previous claims of the ULX being a supercritical accretor. The optical/UV counterpart of Ho II X-1 is explained by a B-type supergiant donor star. Thus, the observations are fully compatible with Ho II X-1 being a close binary consisting of an ≳66 M⊙ black hole accreting matter from an ≃22 M⊙ B-supergiant companion. Furthermore, we propose a possible evolution scenario for the system, suggesting that Ho II X-1 is a potential gravitational wave source progenitor.